Deborah Mawer, editor. Historical Interplay in French Music and Culture, 1860-1960. Routledge, 2018. - Eric Touya de Marenne (Studies in 20th & 21st Century Literature, 2019)
Review of Deborah Mawer, editor. Historical Interplay in French Music and Culture, 1860-1960.
Keywords: French music; 19th century; 20th century; Deborah Mawer; history